5E-Learning Cycle Strategy: Increasing Conceptual Understanding and Learning Motivation - Putra, Febrianto; Nur Kholifah, Ika Yunita; Subali, Bambang; Rusilowati, Ani (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
5E learning cycle strategy was students center oriented learning model. The learning process becomes more meaningful, which are prioritized authentic experience of students, made students become actively participating, able to critical thinking skills and creatively. The phases of the learning cycle 5E consist of engagement, exploration, explanation, elaboration, and evaluation. The purpose of the research was increased learning motivation and conceptual understanding improved by discovery learning due to the 5E learning cycle strategy. The research was conducted at SMA Teuku Umar Semarang. The research has used a qualitative approach. The type of research is classroom action research (CAR). The data analysis technique used a percentage of the learning motivation and the students' understanding concept. The percentage applied discovery learning by both of the first  CAR cycle is 78% and the second CAR cycle is 92%. The conceptual understanding was shown better in the second CAR cycle. The effectiveness discovery learning can be interpreted from the normalized gain. The score of the normalized gain is 0.52. The category of the normalized gain is a medium gain. Students' motivation was increased by both the first cycle is 62%  and the second cycle is 82%.  Based on the decision of the research, it can be concluded that the 5E learning cycle process can influence increased students learning motivation and students understanding the concept not only heat concept but also heat transfer concept